2007
DOI: 10.1785/0120070066
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Regional Variation of Low-Frequency around the Korean Peninsula

Abstract: We studied regional Q 1 Lg at 1 Hz (Q 1 0 ) around the Korean Peninsula based on broadband vertical component seismic records of six Incorporated Research Institutions for Seismology (IRIS) Global Seismographic Network stations and 19 Korean stations of the Korea Institute of Geoscience and Mineral Resources (KI-GAM).Using 177 seismic events with magnitudes between 5.3 and 5.7 and depths less than 50 km, the reversed two station method was applied, and 94 high quality interstation paths were selected from 869 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…However, in a narrow band, such a model may still be a useful and convenient approximation. Several authors have indicated that the measurement of η is generally unstable and poorly constrained [e.g., Xie et al , 2006; Chung et al , 2007]. Our Q Lg model is calculated without a power‐law assumption and, thus, can be used to examine the behavior of η .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a narrow band, such a model may still be a useful and convenient approximation. Several authors have indicated that the measurement of η is generally unstable and poorly constrained [e.g., Xie et al , 2006; Chung et al , 2007]. Our Q Lg model is calculated without a power‐law assumption and, thus, can be used to examine the behavior of η .…”
Section: Resultsmentioning
confidence: 99%
“…Using the M L amplitude catalog, Pei et al [2006] obtained a laterally varying 1 Hz Q model within the crust of northern China. Chung et al [2007] studied the 1 Hz Q Lg around the Korean Peninsula including part of Northeast China and the Sea of Japan. Ford et al [2009] compared the Q Lg images in the Yellow Sea and North Korea region obtained using different methods.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic Q factor has been widely investigated to measure the attenuation characteristics of the medium by using different parts of seismogram such as P waves ( Q P ), S waves ( Q S ), coda waves ( Q C ) and Lg waves ( Q Lg ) (Yoshimoto et al 1993; Chung & Lee 2003; Kim et al 2004; Chung et al . 2005, 2007; Sharma et al 2008; Ma’hood & Hamzehloo 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context it can be mentioned that no earthquakes larger than M 6 were observed in terrestrial S. Korea after 1905 Kim et al, 2004). The low seismicity of S. Korea correlates with low attenuation of P and S waves Kim et al, 2004), and Lg waves Chung et al, 2005Chung et al, , 2007, showing a few regional variations. These studies, however, seem to reflect the values of the deep parts of the crust obtained from long hypocentral distances reaching 160 km for P and S waves, and longer than 150 km for Lg waves.…”
Section: Previous Studies For S Koreamentioning
confidence: 82%